PENGARUH PERBEDAAN SHELTER TERHADAP TINGKAT KELANGSUNGAN HIDUP DAN PERTUMBUHAN LOBSTER AIR TAWAR (Cherax quadricarinatus) - Fadhlan; Muhammad Fauzan Isma; Muhammad Syahril (Jurnal Ilmiah Samudra Akuatika, 2021)
Freshwater crayfish (Cerax quadricarinatus) is a type of shrimp that is widely cultivated in Indonesia and other countries such as Australia, America and England. The high selling price of freshwater crayfish itself is still not comparable to the length of maintenance that takes 6-12 months for lobsters of 50-150 grams / head, and a high mortality rate of up to 30%. The aim of this research is to determine the survival and growth in freshwater crayfish through different shelter treatments. The method used in this study was the CRD method (completely randomized design) with 4 lecturers and 3 replications. In treatment 1 with Paralon pipe shelter, treatment 2 with coconut leaf shelter, treatment 3 with rooster rock shelter and treatment 4 with synthetic grass shelter. The results of the treatment had no significant effect on survival, moulting percentage, absolute weight growth and absolute length growth. There are 3 treatments with a percentage value of 100%, namely the S1, S2, S3 treatment and the lowest in the S4 treatment with a value of 95.83%, the highest moulting percentage is in the S1 treatment which is 0.38% and the lowest is in the S3 treatment which is 0.17 %. The highest absolute weight growth was found in S1 treatment, namely 3.11 gr and the lowest growth in S3 treatment, namely 1.19 gr. The absolute length growth shows the highest result is obtained at S1, namely 0.14 cm, while the lowest absolute length growth is found in S3, namely 0.06 cm.